Ef fect of Rhizoglomus intraradices, Stenotrophomonas rhizophila and Synthetic Fertilizer on Morpho-Productivity and Mineral Content in Cucumber - Lara-Capistrán, Liliana; Reyes-Pérez, Juan J.; Murillo-Amador, Bernardo; Rocha, Jorge; Holguín-Peña, Ramón J.; Preciado-Rangel, Pablo; Hernández-Montiel, Luis G. (REVISTA TERRA LATINOAMERICANA, 2025)
Arbuscular mycorrhizal fungi (AMF) and plant growth promoting rhizobacteria (PGPR) make the application of reduced doses of synthetic fertilizers more ef ficient, stimulating crop growth and productivity. The objective the present study is to evaluate the combined ef fect of Rhizoglomus intraradices, Stenotrophomonas rhizophila and a reduced dose of synthetic fertilizer on morpho-productivity and mineral content of cucumber under greenhouse conditions. A completely randomized design was used with the following treatments: 100% synthetic fertilization (SF); R. intraradices + SF 50 % (Ri+SF50%); S. rhizophila + SF 50% (Sr+SF50%), and R. intraradices + S. rhizophila + SF 50% (Ri+Sr+SF50%) using 200 plants per treatment. The following are calculated as: height (cm), stem diameter (mm), number of leaves and per plant: number of buds, male and female flowers, number of tendrils, greenness index (Iv), number and weight of fruits (g), total weight of fruit/plant (kg), yield (kg m-2), mineral content of N, P, K, Ca and Mn in %, colony forming units (CFU) and mycorrhizal colonization. The data were processed through an analysis of variance according to Tukey’s criterion at 95% confidence. The results indicate that plants with Ri+Sr+FS50% significantly increased (P ≤ 0.001) the height (24.18 cm), stem diameter (6.40 mm), number of leaves (18.35), tendrils (3.10), male flowers (0.4), greenness index (256.95), female flowers (8.90), number of fruits (8.6) and yield (15.92 kg m-2), compared to the application of 100% synthetic fertilizer (FS). The use of beneficial microorganisms in combination with a reduced dose of synthetic fertilizers increases cucumber productivity, therefore, it may constitute a sustainable alternative in agricultural systems, reducing production costs and decreasing environmental pollution, safeguarding human and animal health.